A novel regenerative hydrogen cerium fuel cell for energy storage applications - Hewa,Dewage HARINI; wu,BILLY; Tsoi,ANTHONY; Yufit,VLADIMIR; Offer,GREGORY; Brandon,NIGEL (Journal of Materials Chemistry A, 2015)
A novel regenerative hydrogen cerium fuel cell is presented which has the potential to deliver both low cost and high performance. A 5 cm2 prototype is demonstrated, achieving 148 mW cm−2 when fully charged. Rate determining processes within the cell are identified.